INTERSECTIONAL BARRIERS IN WOMEN’S ENTREPRENEURIAL ASPIRATIONS: A STUDY OF KURUKSHETRA DISTRICT IN HARYANA - Ms. Meenakshi; Singh, Kulvir; Sunil Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Men and women are interconnected and essential for a harmonious society, like as two wheels of a cart, and imply that both man and woman resemble two bulls yoked in a chariot. Both genders’ contributions are vital for a balanced and prosperous society. Traditionally, patriarchal societies like India have limited women's roles to domestic duties and childcare, while men held power and influence, restricting women's access to education, employment, and social advancement. This gender division of labour and societal expectations perpetuated gender inequality and restricted women's opportunities and autonomy. Despite facing numerous obstacles, women have persistently challenged gender norms, demanded equal opportunities, and battled against discrimination. Women’s entry into business evolved from traditional kitchen activities (3P's: Pickle, Powder, Pappad) to modern fields (3E's: Energy, Electronics, Engineering) with education and time. Thus, presents study investigates the experiences, challenges, and opportunities faced by women entrepreneurs of Kurukshetra district of Haryana by employing a triangulation method. Convenience sampling was utilized to select 30 participants, comprising women entrepreneurs. The findings highlight the intersectional barriers, including socio-cultural norms, financial constraints, and lack of institutional support, that hinder women's entrepreneurial aspirations. Notably, the study reveals the resilience and adaptability of women entrepreneurs in navigating these challenges and leveraging community networks and government initiatives to foster business growth. The research contributes to the existing literature on women's entrepreneurship in rural India, emphasizing the need for targeted policy interventions, capacity-building programs, and inclusive support systems. The study's conclusions inform strategies for promoting women's economic empowerment and entrepreneurship development in Haryana, with implications for similar contexts globally.